From the formal and narrative characteristics to the artistic value of the fashion film: a proposal from the Fine Arts - Garre Sánchez, Cristina (2023)
The fashion film is an audiovisual creation that is actively used in the Fashion Industry with the purpose of serving as a brand communication strategy. It is considered as a piece of branded content and its definition and characteristics are being established in the scientific field. The main objective of this literature review is to bring together the knowledge generated on the characteristics of the fashion film in terms of its formal and narrative features. The secondary objective is to express the artistic value of the fashion film from an artistic perspective. The fashion film is not only a moving image, but also a moving plastic image, which involves the artistic-plastic value of artistic creation and composition.